2017
DOI: 10.1007/978-3-319-58274-0_21
|View full text |Cite
|
Sign up to set email alerts
|

Serendipitous Recommendations Through Ontology-Based Contextual Pre-filtering

Abstract: Context-aware Recommender Systems aim to provide users with better recommendations for their current situation. Although evaluations of recommender systems often focus on accuracy, it is not the only important aspect. Often recommendations are overspecialized, i.e. all of the same kind. To deal with this problem, other properties can be considered, such as serendipity. In this paper, we study how an ontology-based and context-aware pre-filtering technique which can be combined with existing recommendation algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Some recommender systems suffer from their over-specialization (sometimes referred to as a serendipity problem). It is observed when the RS produces recommendations with minimal novelty, i.e., all of the same kind [22]. Recently, there is also an increasing interest in privacy awareness when handling user data and explainability of recommendations [23], [24].…”
Section: Related Workmentioning
confidence: 99%
“…Some recommender systems suffer from their over-specialization (sometimes referred to as a serendipity problem). It is observed when the RS produces recommendations with minimal novelty, i.e., all of the same kind [22]. Recently, there is also an increasing interest in privacy awareness when handling user data and explainability of recommendations [23], [24].…”
Section: Related Workmentioning
confidence: 99%
“…They showed that usage of such micro profiles gave a significant improvement in the prediction accuracy in the movie domain while considering time as a context variable. Pre-filtering approach which utilizes ontological user profiles was proposed by Karpus et al [6] Contextual post-filtering applies context after traditional recommendation process. It means that from a predicted set of recommendations we select just those that match current user context.…”
Section: Related Workmentioning
confidence: 99%